2009
DOI: 10.1007/s00586-009-1111-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of excisional surgeries for the patients with spinal metastases

Abstract: To evaluate the outcome of the excisional surgeries (en bloc/debulking) in spinal metastatic treatment in 10 years. A total of 131 patients (134 lesions) with spinal metastases were studied. The postoperative survival time and the local recurrence rate were calculated statistically. The comparison of the two procedures on the survival time, local recurrence rate, and neurologic change were made. The median survival time of the en bloc surgery and the debulking surgery was 40.93 and 24.73 months, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
3
30
0
7
Order By: Relevance
“…Due to the large difference in the number of patients in our series who underwent the various surgical approaches [posterior (n = 105) vs. anterior (n = 3) vs. combined (n = 13)], we were not able to perform any meaningful statistics to make comparisons with our outcome variables. However, Li et al [19] showed that en bloc surgery (n = 32) could achieve a lower local recurrence rate than the debulking surgery (n = 99), but with similar survival, neurological salvage, and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large difference in the number of patients in our series who underwent the various surgical approaches [posterior (n = 105) vs. anterior (n = 3) vs. combined (n = 13)], we were not able to perform any meaningful statistics to make comparisons with our outcome variables. However, Li et al [19] showed that en bloc surgery (n = 32) could achieve a lower local recurrence rate than the debulking surgery (n = 99), but with similar survival, neurological salvage, and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, en bloc surgical resections are technically demanding, are associated with higher complication rates, and do not necessarily increase OS in patients with MSCC 1,3,4,13,18) . Our patients underwent palliative tumor removal using either posterior or 360掳 surgery, because all patients had Tokuhashi scores ranging from 0 to 11 were candidates for palliative surgery 18) .…”
Section: Comparison Of Surgical Methodsmentioning
confidence: 99%
“…That means en bloc resection would reduce the morbidity associated with local recurrence and revision surgery compared with curettage. However, the two procedures resulted in a similar survival outcome, neurological salvage, and incidence of complications [9]. Moreover, total spondylectomy is a procedure with strict principles that are difficult to fully achieve.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we recommend preoperative embolization for every patient if possible. Surgical treatment of thyroid cancer has been found to be important and effective in several recent studies [2,3,5,8,9]. Operations for patients with thyroid cancer spinal metastases should be more aggressive, which is in contrast to more traditional opinions in the field.…”
Section: Discussionmentioning
confidence: 99%